Relationship of Knowledge of Mother with the Level of Language Development in Children Aged 2-3 Years in Puskesmas Padang Panyang, Nagan Raya - Anasril Anasril; Muhammad Husaini; Bustami Bustami; Amiruddin Amiruddin (Universitas Teuku Umar, 2021)
Stimulation of growth and development, especially language development in children, needs to be done to improve children's ability to speak in accordance with the level of development. The lack of information obtained by mothers about the importance of language stimulation for children causes mothers to consider it normal when a child is able to speak too late. The purpose of this study was to determine the relationship between maternal knowledge and the level of language development in children aged 2-3 years in Puskesmas Pandang Panyang, Nagan Raya. This research is analytical with a cross-sectional study design. The number of samples is 100 people taken randomly. The results showed that there was a significant relationship between maternal knowledge about language stimulation and language development in children aged 2-3 years with a value of p = 0.000. With Prevalence ratio (PR), namely 31.89. It is recommended that parents increase their knowledge of language stimulation in order to realize language development according to age and child